(untitled) (Journal of Hama University, 2020)
This study aimes to study the stability of the general index of Damascus Stock Exchange during the period 2010-2019, in addition to measuring the index risk using the value-at-risk model, and studying the impact of this risk on both the returns and risk of shares of the private commercial banks operating in Syria for the 2010 period 2019. The most important finding of the study is that the general activity of Damascus market during the period in question was unstable. Rather, it was increasing especially between 2017 and 2019. The statistical study also showes that there was no impact of the index risks on the returns and risk of the shares of these banks; nor, it was clear, was there any reversed relationship between the risk of the index using the value at risk and the returns of these banks on shares.